Do Narcissists Tend to Reduce Interpersonal Conflicts in Organizations? The Effects of Abusive Supervision on Ostracism and Interpersonal Conflicts - TAHIRA RASHEED; ARSHAD ZAHEER; SADAF MANZOOR (Journal of Economics and Behavioral Studies, 2021)
This study aims to examine the relationship between abusive supervision (ABS) and interpersonal conflicts (IPC) with the mediating role of key variables, ostracism (OST), and moderating role of narcissism (NAR) among the service industry of Pakistan. A convenient sampling technique is used for data collection from employees of public and private commercial banks of Pakistan through a self-administered questionnaire. A total of 650 questionnaires were distributed with a response rate of 38%, as 247 valid responses were received. The findings validated the proposed model with a significant correlation between ABS and OST, provoking IPC in organizations. The mediating role of OST is examined. Full mediation between ABS and IPC is revealed. Moreover, a subordinate’s NAR moderated and weakened the positive relation of ABS and OST and OST and IPC. This study will help employers devise a methodology to minimize IPCs among employees after discovering the reasons for conflicts among them. One reason specified by this theory is ABS. Employers can look upon this study to mitigate conflict in their organization, hampering their strategies to progress. Eventually, this study will contribute to reducing a major threat of the organizations where their manpower is enforced towards burnouts due to the factors discussed here.